Physiological responses of native and crossbred sheep to climatic stress under semi-arid conditions* - ASHUTOSH, ASHUTOSH; DHANDA, O P; KUNOU, R L (The Indian Journal of Animal Sciences, 2014)
Rectal temperature, pulse rate and respiration rate in native (Chokla) lmd Avivastra (Chokla x Rambouillet) sheep were investigated during different seasons kept under semi-arid conditions after following standard procedures. The results revealed that there exists a significant difference in rectal temprature in animals of both the breeds between seasons. However, the rectal temperature in native and crossbred animals did not differ significantly in summer season. Sigmficant diurnal variation was observed in crossbreds in all the seasons' except spring. A significantly higher(P